Leibniz algebras of dimension 3 over finite fields - Yashchuk, V.S. (Доповіді НАН України, 2018)
The first thing in the study of all types of algebras is the description of algebras having small dimensions. Unlike the
simpler cases of 1- and 2-dimensional Leibniz algebras, the structure of 3-dimensional Leibniz algebras is more complicated.
We consider the structure of Leibniz algebras of dimension 3 over a finite field. In some cases, the structure
of the algebra essentially depends on the characteristic of the field. In others, it depends on the solvability of specific
equations in the field, and so on. Першим кроком у вивченні всіх типів алгебр є опис таких алгебр, які мають малі вимірності. На відміну від
більш простих випадків одно- і двовимірних алгебр Лейбніца, структури тривимірних алгебр Лейбніца
складніші. У роботі розглядається структура алгебр Лейбніца вимірності 3 над скінченним полем. У деяких випадках структура алгебр суттєво залежить від характеристики поля, в інших — від можливості
розв'язання конкретних рівнянь у полі і т. п. Первым шагом в изучении всех типов алгебр является описание таких алгебр, которые имеют малые размерности. В отличие от более простых случаев одно- и двумерных алгебр Лейбница, структуры трехмерных алгебр Лейбница сложнее. В работе рассматривается структура алгебр Лейбница размерности 3 над
конечным полем. В некоторых случаях структура алгебры зависит от характеристики поля, в других — от
разрешимости конкретных уравнений в поле и т. п.